POLYMERIZATION EFFICIENCY OF TWO DUAL-CURE CEMENTS THROUGH DENTAL CERAMICS - Volkan Turp; Deger Ongul; Pinar Gultekin; Ozgur Bultan; Burcin Karatasli; Elif Pak Tunc (Istanbul University, 2015)
Purpose: The aim of this study was to evaluate the effect of thickness of zirconia on curing efficiency of resin cements. Materials and Methods: 4 discs with 4.0 mm in diameter were prepared from non-HIP translucent zirconia blocks using a CAD/CAM system and feldspathic ceramic was layered onto discs. Thus, 4 ceramic disc samples were fabricated: (G) 0.5 mm zirconia- as a control group, (G1) 0.5 mm zirconia and 0.5 mm feldspathic, (G2) 1.0 mm zirconia and 0.5 mm feldspathic and (G3) 2.0 mm zirconia and 0.5 mm feldspathic ceramic layer. 2 different dual cure cements were polymerized using a LED curing unit. Degree of conversion was evaluated using Vickers Hardness Test and depths of cure of samples were measured. Data were analyzed statistically using One-way ANOVA and Tukey's HSD test (p<0.05). Results: Microhardness and depth of cure values were different under same thickness of ceramic discs for two resin cements. As the thickness of the zirconia discs increased, the microhardness values and depth of cure decreased. Conclusion: Photocuring time cannot be the same for all clinical conditions, under thicker zirconia restorations (>2.0 mm), an extended period of light curing or a light unit with a high irradiance should be used.